AN ANALYSIS OF TRAINING REQUIREMENTS FOR TEACHERS IN THE APPLICATION OF ARTIFICIAL INTELLIGENCETO SCIENTIFIC WRITING - Amrullah, Silmi; Azhari, Alim Bahri; Wardi, Sahro; Kasim, Juanda (Balai Diklat Keagamaan Jakarta, 2025)
The advancement of artificial intelligence (AI) presents significant opportunities for teachers to enhance their scientific writing skills. Nevertheless, optimal use of AI remains limited by insufficient digital literacy, technical proficiency, and understanding of ethical considerations. To address these challenges, this study investigates the demand for scientific writing training that incorporates AI and identifies barriers to its effective implementation. A mixed-methods approach was employed, utilising questionnaires with 135 teachers and interviews with 8 to 10 teachers. The findings revealed that 53% of participants require structured training encompassing writing practice, reflective activities, mastery of key concepts, and the integration of AI in scientific article preparation. To frame these results, the study draws on three theoretical frameworks: experiential learning theory, with 71.25% of responses rated as high; adult learning theory (andragogy), with 83.33% of responses rated as very high; and Asilomar AI theory, with 81.81% of responses rated as very high. In particular, key challenges identified include risks of plagiarism, concerns about data accuracy, limited contextual understanding, and issues related to academic ethics. In response, the study proposes a comprehensive training model that integrates experience-based learning, andragogical principles, and AI ethics. Abstrak Perkembangan kecerdasan buatan memberikan peluang baru bagi guru dalam meningkatkan kemampuan penulisan karya ilmiah, namun pemanfaatannya belum optimal akibat keterbatasan literasi digital, keterampilan teknis, dan pemahaman etis. Penelitian ini bertujuan menganalisis kebutuhan pelatihan penulisan ilmiah dengan pemanfaatan kecerdasan buatan serta mengidentifikasi hambatan dalam praktiknya. Metode yang digunakan adalah pendekatan campuran dengan melibatkan 135 guru melalui angket dan 8-10 guru melalui wawancara. Hasil penelitian menunjukkan bahwa mayoritas guru dengant presentase 53% sangat membutuhkan pelatihan terstruktur yang mencakup praktik menulis, refleksi, penguasaan konsep, dan integrasi kecerdasan buatan dalam praktik menulis artikel ilmiah. Penelitian ini didasari tiga teori yaitu (1) teori pembelajaran eksperiensial dengan hasil rekapituliasi tanggapan responden berada pada kategori tinggi, dengan persentase bobot 71,25%, (2) terori pempelajaran orang dewasa: andragogi dengan hasil rekapituliasi tanggapan responden berada pada kategori sangat tinggi, dengan persentase bobot 83,33%, dan (3) teori Asilomar artificial intelligence dengan hasil rekapituliasi tanggapan responden berada pada kategori sangat tinggi, dengan persentase bobot 81,81%. Adapun tantangan dan hambatan yang dihadapi responden meliputi risiko plagiarisme, akurasi data, pemahaman konteks, serta isu etika akademik. Penelitian ini menawarkan kerangka baru dengan mengintegrasikan teori pembelajaran berbasis pengalaman, prinsip andragogi, dan prinsip etika kecerdasan buatan untuk merancang model pelatihan yang lebih komprehensif.